Design, analysis and user acceptance of architectural design education in learning system based on knowledge management theory. Issue 11 (2016) - Wu, Yun-Wu; Lin, Yu-An; Wen, Ming-Hui; Perng, Yeng-Hong; Hsu, I-Ting
No abstract available